Bet v 1-displaying elastin-like polypeptide nanoparticles induce a strong humoral and weak CD4+ T-cell response against Bet v 1 in a murine immunogenicity model - van Strien, Jolinde; Warmenhoven, Hans; Logiantara, Adrian; Makurat, Max; Aglas, Lorenz; Bethanis, Athanasios; Leboux, Romain; van Rijt, Leonie; MacKay, J. Andrew; van Schijndel, Johannes W.; Schneider, Gregory; Olsthoorn, René; et al. (Frontiers in Immunology, 2022)
There is growing concern about the toxicity of colloidal aluminum salts used as adjuvants in subcutaneous allergen immunotherapy (SCIT). Therefore, alternative adjuvants and delivery systems are being explored to replace alum in SCIT. We applied micellar elastin-like polypeptides (ELPs), a type of self-assembling protein, to replace alum as vaccine adjuvant in birch pollen SCIT. ELP and an ELP-Bet v 1 fusion protein were expressed in E. coli and purified by immuno-affinity chromatography and inverse-transition cycling (ITC). Nanoparticles self-assembled from ELP and a 9:1 ELP/ELP-Bet v 1 mixture were characterized by using dynamic light scattering and atomic force microscopy. Allergenicity was assessed by measuring mediator release from rat basophilic leukemia cells transformed with the human FcεR1 and sensitized with sera derived from human birch pollen allergic patients. Humoral and T-cell immunity were investigated by immunizing naïve mice with the ELP/ELP-Bet v 1 nanoparticles or alum-adsorbed Bet v 1, both containing 36 µg Bet v 1. ELP and ELP/ELP-Bet v 1 self-assembled at 37 °C into spherically shaped micelles with a diameter of ~45 nm. Multivalent display on the ELP micelle surface made Bet v 1 hypo-allergenic (10-fold). Compared to alum-adsorbed Bet v 1, ELP/ELP-Bet v 1 nanoparticles induced stronger IgG responses with an earlier onset. Additionally, ELP/ELP-Bet v 1 did not induce Th2 skewing cytokines and IgE. The hypoallergenic character and strong humoral immune response in the absence of a Th2-skewing T-cell response make ELP-based nanoparticles a promising candidate to replace alum in SCIT.